Effect of Macro and Micro Polypropylene Fibers on the Flexural Behavior of RC Slabs - Fariq, Miaad S.; Kakshar, Feirusha S.M. (Zanco Journal of Pure and Applied Sciences, 2025)
This research highlights the effect of the micro polypropylene fibers (mPPF), macro polypropylene fibers (MPPF), and hybrid fibers (combination of mPPF and macro steel fiber at the rate of half) on the flexural strength of the one-way reinforced concrete (RC) slabs. The optimum fiber content is considered based on the ultimate flexural load and mechanical properties. A total of 10 simply supported one-way RC slabs in dimensions 1100 × 400 × 80 mm (length × width × thickness) were prepared and tested under a four-point bending test to investigate their response to first crack load, ultimate load, deflection, and strain. The dosage of the fibers was 0.5%, 1%, and 1.5% by total volume of concrete. Also, the aspect ratios were 375 for mPPFs, 50 for MPPFs, 35 for macro steel fibers. The test results revealed that the flexural stiffness and crack resistance of the one-way RC slabs were improved compared to the control slab. Though the ultimate flexural load increased by 29.73% for the slab with mPPF at 0.5% dosage, 32.46% for the slab with MPPF at 0.5% dosage. The slab with steel fiber + mPPF at 1.5% dosage demonstrated an increased ultimate flexural load of 28.2% compared to the control slab, while the cracks widened. The load-deflection curve of the slab with mPPF at 0.5% dosage displayed the most elastic one-way RC slab among all the slabs, as it enhanced the first crack load by 112%. The load-deflection curve of MPPFRC slabs and the slabs with hybrid fibers displayed the gradual decline in post-cracking behavior.